Nickel-iron-based high-temperature alloy material and aging treatment method thereof
The grain boundary and γ′ phase precipitation characteristics of nickel-iron-based high-temperature alloy were controlled through two heat treatment methods, which solved the problem of high strength but difficulty in deformation under high alloying degree, and achieved the improvement of the good durable performance and production efficiency of the alloy, reducing the production costs.
Patent Information
- Application Number
- CN202411432013.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-01-14
AI Technical Summary
Nickel-iron-based high-temperature alloy materials have high strength but are difficult to deform under high alloying degree, resulting in increased deformation resistance during production, increasing production difficulty and cost, and prone to cracking problems, limiting their application.
Two heat treatment methods are adopted. The first heat treatment is used to heat the nickel-iron-based high-temperature alloy to above the γ′ dissolution temperature and quickly cool it. The second heat treatment is heated to 80-200℃ and then air-cooled and quickly cooled to control grain boundary carbides and The precipitation characteristics of the γ′ phase make the alloy in an under-age state and reduce the deformation resistance.
The alloy is strengthened to precipitate by controlling the cooling method, hindering dislocation movement, improving long-term performance, reducing production difficulty, extending service life, reducing crack formation, improving production efficiency and reducing costs.
Smart Images

Figure CN119307836A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of high-temperature alloys, and in particular relates to a nickel-iron-based high-temperature alloy material and an aging treatment method thereof. Background Art
[0002] As an important pillar in the energy sector, the coal-fired power industry plays a vital role in ensuring global electricity supply and economic development. Although the scale of new energy installed capacity continues to increase, the advantage of coal-fired power units is that their electromechanical characteristics can provide important support for the stable balance of the power system. Coal-fired power units are of great significance for ensuring power supply reliability. Focusing on the dual carbon goals, the coal-fired power industry should focus technological innovation on improving unit efficiency, reducing pollutant emissions, and reducing resource waste. Materials and manufacturing processes are the key technical cores for the development of high-parameter ultra-supercritical units. The environment in which the superheater / reheater components are located in power station boilers is very complex, and the requirements for the comprehensive performance of materials are high. Designing and preparing cost-effective high-temperature alloys that meet the service environment requirements is of great significance to the development of high-parameter ultra-supercritical units.
[0003] At present, nickel-iron-based high-temperature alloys are important candidate materials for the preparation of boiler final superheater / reheater components, and heat treatment is an important means to regulate their comprehensive performance. Nickel-iron-based high-temperature alloy materials are strengthened by precipitation strengthening as the main method and solid solution strengthening as the auxiliary method. During the aging treatment process, the microstructure, such as the number, size, and shape of the precipitated phases within the grains, and the morphology and number of the precipitated phases at the grain boundaries, will change significantly with the changes in the treatment process, which has a significant impact on the alloy's cold and hot processing performance, welding performance, and long-term durability.
[0004] With the improvement of the parameters of advanced ultra-supercritical units, higher service requirements are put forward for the materials of key hot end components. Nickel-based and nickel-iron-based alloys have become important candidate materials for high-temperature structural parts of coal-fired units. Such materials have a high proportion of alloying elements and high alloy strength. However, high alloying also increases the deformation resistance of the alloy during hot and cold processing, increasing the production difficulty of important links such as rolling and straightening in the production process of alloy pipes, and increasing production costs. Moreover, the high resistance during deformation causes problems such as cracking of the alloy, which seriously restricts the production and practical application of the alloy. Summary of the invention
[0005] In order to solve the problems existing in the prior art, the purpose of the present invention is to provide a nickel-iron-based high-temperature alloy material and an aging treatment method thereof. The present invention can solve the problem that the current high-temperature alloy materials with a high degree of alloying have high strength but are difficult to deform.
[0006] The technical solution adopted by this hair is as follows:
[0007] An aging treatment method for a nickel-iron-based high-temperature alloy material comprises:
[0008] The first heat treatment: the nickel-iron-based high-temperature alloy is heated to 150-250°C above the γ′ melting temperature, and then kept warm for 0.5-3.0 hours, and then quickly cooled after the end of the heat preservation; wherein the heating rate is 5-20°C / min;
[0009] Second heat treatment: heat the nickel-iron-based high-temperature alloy after the first heat treatment to 80-200°C above the γ′ melting temperature, then keep it warm for 0.5-3.0h, air cool it for 2-5min after the insulation, and then cool it quickly to complete the aging treatment; the heating rate is 5-20°C / min.
[0010] Preferably, the rapid cooling method in both the first heat treatment and the second heat treatment is water quenching.
[0011] Preferably, after the first heat treatment, the grain size of the nickel-iron-based high-temperature alloy is 100-160 μm, the volume fraction of grain boundary carbides is less than 4% and is primary carbide, and the size of intracrystalline γ′ phase precipitation is no more than 3 nm.
[0012] Preferably, after the second heat treatment, the nickel-iron-based high-temperature alloy matrix is an austenite structure, the grain size is 110-135 μm, and the grain boundary carbides are MC and M 23 C6, the volume fraction of carbides is less than 10%, the volume fraction of the intracrystalline γ′ phase precipitation is less than 15%, and the size of the precipitation phase is 14-20nm.
[0013] Preferably, the start time of air cooling is calculated from the time when the surface of the nickel-iron-based high-temperature alloy begins to cool down, and the end time of air cooling is the time point when the nickel-iron-based high-temperature alloy enters the rapid cooling medium.
[0014] Preferably, when the sum of the mass percentages of the elements Ti and Al in the nickel-iron-based high-temperature alloy is ≥4.0%, the air cooling time in the second heat treatment is not longer than 4 minutes.
[0015] Preferably, after the second heat treatment, the nickel-iron-based high-temperature alloy is in an under-aged state.
[0016] The present invention also provides a nickel-iron-based high-temperature alloy material, which is prepared by the aging treatment method of the present invention as described above.
[0017] Preferably, the components of the nickel-iron-based high-temperature alloy include, in mass percentage: C: 0.04% to 0.09%, Si: ≤0.8%, Mn: ≤0.3%, Cr: 15% to 25%, P: ≤0.02%, Ni: 35% to 48%, Mo: 0.3% to 0.9%, W: ≤0.7%, Nb: ≤1.5%, Ti: 1.0% to 3.0%, Al: 1.3% to 3.0%, Co: ≤3.0%, Zr: ≤0.05%, B: ≤0.02%, and the balance is Fe.
[0018] Preferably, the room temperature yield strength of the nickel-iron-based high temperature alloy is not less than 300 MPa, the elongation is not less than 30%, and the room temperature impact toughness is not less than 80 J / cm 2 .
[0019] The present invention has the following beneficial effects:
[0020] The aging treatment method of the nickel-iron-based high-temperature alloy material proposed in the present invention allows the main strengthening phase in the nickel-iron-based high-temperature alloy to be partially separated out by controlling the cooling, so that it is in an under-aging state. On the one hand, the alloy is strengthened, and the fine and dispersed second phase particles interact with dislocations and hinder the movement of dislocations to achieve the purpose of precipitation strengthening, so that the nickel-iron-based high-temperature alloy has good long-term durability. On the other hand, it can reduce the deformation resistance of the nickel-iron-based high-temperature alloy, greatly increase the forming limit of the nickel-iron-based high-temperature alloy, reduce the softening annealing process of the material, reduce the difficulty of rolling and straightening processes, reduce crack formation and improve surface quality, extend the service life of the nickel-iron-based high-temperature alloy and its components, improve production efficiency, and reduce production costs. Therefore, the present invention can provide a new way and method for strengthening and toughening the nickel-iron-based high-temperature alloy used for key hot end components of high-parameter ultra-supercritical units, which is conducive to promoting the actual application process of the alloy. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0022] Figure 1 This is the metallographic morphology of the nickel-iron-based high-temperature alloy after heat treatment in Example 1 of the present invention.
[0023] Figure 2 This is the SEM grain boundary morphology of the nickel-iron based high temperature alloy after heat treatment in Example 1 of the present invention.
[0024] Figure 3This is the SEM intragranular strengthening phase morphology of the nickel-iron based high temperature alloy after heat treatment in Example 1 of the present invention.
[0025] Figure 4 This is a flattening experiment of the nickel-iron-based high-temperature alloy tube after heat treatment in Example 1 of the present invention.
[0026] Figure 5 This is the metallographic morphology of the nickel-iron-based high-temperature alloy after heat treatment in Example 2 of the present invention.
[0027] Figure 6 This is the SEM grain boundary morphology of the nickel-iron based high temperature alloy after heat treatment in Example 2 of the present invention.
[0028] Figure 7 This is the SEM intragranular strengthening phase morphology of the nickel-iron based high temperature alloy after heat treatment in Example 2 of the present invention.
[0029] Figure 8 This is a flattening experiment of the nickel-iron-based high-temperature alloy tube after heat treatment in Example 2 of the present invention.
[0030] Fig. 9 This is the metallographic morphology of the nickel-iron-based high-temperature alloy after heat treatment in Example 3 of the present invention.
[0031] Fig.10 This is the SEM grain boundary morphology of the nickel-iron based high temperature alloy after heat treatment in Example 3 of the present invention.
[0032] Fig.11 This is the SEM intragranular strengthening phase morphology of the nickel-iron based high temperature alloy after heat treatment in Example 3 of the present invention.
[0033] Fig.12 This is a flattening experiment of the nickel-iron-based high-temperature alloy tube after heat treatment in Example 3 of the present invention.
[0034] Fig.13 This is the metallographic morphology of the nickel-iron-based high-temperature alloy after heat treatment in Example 4 of the present invention.
[0035] Fig.14 This is the SEM grain boundary morphology of the nickel-iron based high temperature alloy after heat treatment in Example 4 of the present invention.
[0036] Fig.15 This is the SEM intragranular strengthening phase morphology of the nickel-iron based high temperature alloy after heat treatment in Example 4 of the present invention.
[0037] Fig.16 This is a flattening experiment of the nickel-iron-based high-temperature alloy tube after heat treatment in Example 4 of the present invention.
[0038] Fig.17 This is the SEM intragranular strengthening phase morphology of the nickel-iron-based high-temperature alloy after heat treatment in Comparative Example 1 of the present invention.
[0039] Fig.18 This is a flattening experiment of the nickel-iron-based high-temperature alloy tube after heat treatment in Comparative Example 1 of the present invention.
[0040] Fig.19 This is the SEM intragranular strengthening phase morphology of the nickel-iron-based high-temperature alloy after heat treatment in Comparative Example 2 of the present invention.
[0041] Fig. 20 This is a flattening experiment of the nickel-iron-based high-temperature alloy tube after heat treatment in Comparative Example 2 of the present invention. DETAILED DESCRIPTION
[0042] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.
[0043] The aging treatment method of the nickel-iron-based high-temperature alloy material of the present invention comprises the following steps:
[0044] Step 1: heating the nickel-iron-based high-temperature alloy to 150-250°C above the γ′ melting temperature, and then keeping the temperature for 0.5-3.0 hours. After the temperature is kept, the alloy is quickly cooled to room temperature by water quenching; wherein the heating rate is 5-20°C / min;
[0045] Step 2: Heat the nickel-iron-based high-temperature alloy treated in step 1 to 80-200°C above the γ′ melting temperature, and then keep it warm for 0.5-3.0h. After the insulation is completed, take out the sample and air cool it for 2-5min, and then quickly cool it to room temperature by water quenching; wherein the heating rate is 5-20°C / min.
[0046] The aging treatment method of the present invention is applicable to the nickel-iron-based high-temperature alloy with the following components, wherein the components in the nickel-iron-based high-temperature alloy include, by mass percentage: C: 0.04% to 0.09%, Si: ≤0.8%, Mn: ≤0.3%, Cr: 15% to 25%, P: ≤0.02%, Ni: 35% to 48%, Mo: 0.3% to 0.9%, W: ≤0.7%, Nb: ≤1.5%, Ti: 1.0% to 3.0%, Al: 1.3% to 3.0%, Co: ≤3.0%, Zr: ≤0.05%, B: ≤0.02%, and the balance is Fe.
[0047] For the nickel-iron-based high-temperature alloy with the above composition, after treatment in step 1, the grain size of the nickel-iron-based high-temperature alloy is 100-160μm, the volume fraction of grain boundary carbides is less than 4% and is primary carbides, and the size of the γ′ phase precipitation in the grain is not greater than 3nm. After treatment in step 2, the alloy matrix is austenite, the grain size is 110-135μm, and the grain boundary carbides are MC and M 23 C6, the volume fraction of carbides is not more than 10%, the volume fraction of the intracrystalline γ′ phase precipitation is not more than 15%, and the size of the precipitation phase is 14-20nm.
[0048] In the above step 2, the start time of air cooling is calculated from the time when the temperature of the material surface begins to drop, and the end time of air cooling is the time point when the material enters the rapid cooling medium.
[0049] When the mass percentage of the elements Ti and Al components in the nickel-iron-based high-temperature alloy satisfies Ti+Al≥4.0%, the air cooling time in step 2 is not longer than 4 minutes.
[0050] The nickel-iron-based high-temperature alloy material obtained by the aging treatment method of the present invention is in an under-aged state, with a room temperature yield strength of not less than 300MPa, an elongation of not less than 30%, and a room temperature impact toughness of not less than 80J / cm 2 .
[0051] Example 1
[0052] In this embodiment, the alloy composition is prepared according to the mass percentage. The specific content of each component of the nickel-iron-based high-temperature alloy material sample in this embodiment is as follows: C: 0.05%, Si: 0.6%, Mn: 0.1%, Cr: 20%, P: 0.01%, Ni: 40%, Mo: 0.3%, W: 0.2%, Nb: 1.0%, Ti: 1.9%, Al: 1.8%, Co: 1.0%, Zr: 0.01%, B: 0.01%, and the balance is Fe. The nickel-iron-based high-temperature alloy sample with the above composition is heated to 240°C above the γ′ dissolution temperature, and then kept warm for 1 hour. After the insulation is completed, it is quickly cooled to room temperature by water quenching; wherein the heating rate is 10°C / min. Then the nickel-iron-based high-temperature alloy sample is heated again to 200°C above the γ′ dissolution temperature, and then kept warm for 2 hours. After the insulation is completed, the sample is taken out and air-cooled for 3 minutes, and then quickly cooled to room temperature by water quenching; wherein the heating rate is 10°C / min.
[0053] Figure 1 The metallographic morphology of the nickel-iron-based high-temperature alloy after aging heat treatment in Example 1 shows that the matrix of the nickel-iron-based high-temperature alloy obtained in this example is austenite, and its grain size is 121 μm. The alloy was subjected to microstructure display using copper sulfate solution, and the grain boundary SEM morphology is as follows: Figure 2 As shown, it can be seen that the grain boundary has less MC and M23 C6 carbide phase, carbide volume fraction is 3%. The alloy was analyzed by nitroglycerin solution, and the SEM morphology of the intragranular strengthening phase is as follows: Figure 3 As shown, the size of the precipitated phase in the crystal is 19nm, and the volume fraction is 13.6%. The alloy tube is flattened according to the "GB / T 246 Metal Material Tube Flattening Test Method". The results are as follows Figure 4 As shown, there are no cracks or fissures on the inner and outer surfaces of the sample.
[0054] Example 2
[0055] In this embodiment, the alloy composition is prepared according to the mass percentage. The specific contents of each component of the nickel-iron-based high-temperature alloy material sample in this embodiment are as follows: C: 0.08%, Si: ≤0.4%, Mn: 0.2%, Cr: 22%, P: 0.002%, Ni: 45%, Mo: 0.3%, W: 0.2%, Nb: 0.3%, Ti: 1.9%, Al: 1.9%, Co: 2.0%, Zr: 0.01%, B: 0.01%, and the balance is Fe. The nickel-iron-based high-temperature alloy sample with the above composition is heated to 200°C above the γ′ dissolution temperature, and then kept warm for 1.5 hours. After the insulation is completed, it is quickly cooled to room temperature by water quenching; wherein the heating rate is 15°C / min. Then the nickel-iron-based high-temperature alloy sample is heated again to 150°C above the γ′ dissolution temperature, and then kept warm for 3 hours. After the insulation is completed, the sample is taken out and air-cooled for 4 minutes, and then quickly cooled to room temperature by water quenching; wherein the heating rate is 15°C / min.
[0056] Figure 5 The metallographic morphology of the nickel-iron-based high-temperature alloy of Example 2 after failure heat treatment is shown in Figure 2. It can be seen that the matrix of the nickel-iron-based high-temperature alloy obtained in Example 2 is an austenite structure with a grain size of 113 μm. The alloy was subjected to microstructure display using a copper sulfate solution. The grain boundary SEM morphology is shown in Figure 2. Figure 6 As shown, it can be seen that the grain boundary has less MC and M 23 C6 carbide phase, carbide volume fraction is 4%. The alloy was analyzed by nitroglycerin solution, and the SEM morphology of the intragranular strengthening phase is as follows: Figure 7 As shown in the figure, the size of the precipitated phase in the crystal is 18nm and the volume fraction is 14.1%. The alloy tube was flattened according to the "GB / T 246 Metal Material Tube Flattening Test Method". The results are as follows Figure 8 As shown, there are no cracks or fissures on the inner and outer surfaces of the sample.
[0057] Example 3
[0058] In this embodiment, the alloy composition is prepared according to the mass percentage. The specific content of each component of the nickel-iron-based high-temperature alloy material sample in this embodiment is as follows: C: 0.08%, Si: ≤0.3%, Mn: 0.1%, Cr: 18%, P: 0.007%, Ni: 48%, Mo: 0.3%, W: 0.5%, Nb: 0.2%, Ti: 2.2%, Al: 2.1%, Co: 2.0%, Zr: 0.02%, B: 0.01%, and the balance is Fe. The nickel-iron-based high-temperature alloy sample with the above composition is heated to 180°C above the γ′ dissolution temperature, and then kept warm for 2.5 hours. After the insulation is completed, it is quickly cooled to room temperature by water quenching; wherein the heating rate is 5°C / min. Then the nickel-iron-based high-temperature alloy sample is heated again to 100°C above the γ′ dissolution temperature, and then kept warm for 2 hours. After the insulation is completed, the sample is taken out and air-cooled for 2 minutes, and then quickly cooled to room temperature by water quenching; wherein the heating rate is 5°C / min.
[0059] Fig. 9 The metallographic morphology of the alloy of Example 3 after heat treatment shows that the alloy matrix is austenite with a grain size of 118 μm. The alloy was analyzed by copper sulfate solution, and the grain boundary SEM morphology is as follows: Fig.10 As shown, it can be seen that the grain boundary has less MC and M 23 C6 carbide phase, carbide volume fraction is 6%. The alloy was analyzed by nitroglycerin solution, and the SEM morphology of the intragranular strengthening phase is as follows: Fig.11 As shown in the figure, the size of the precipitated phase in the crystal is 14nm and the volume fraction is 12.5%. The alloy tube was flattened according to the "GB / T 246 Metal Material Tube Flattening Test Method". The results are as follows Fig.12 As shown, there are no cracks or fissures on the inner and outer surfaces of the sample.
[0060] Example 4
[0061] In this embodiment, the alloy composition is prepared according to the mass percentage. The specific content of each component of the nickel-iron-based high-temperature alloy material sample in this embodiment is as follows: C: 0.09%, Si: 0.8%, Mn: 0.3%, Cr: 19%, P: 0.02%, Ni: 39%, Mo: 0.8%, W: 0.4%, Nb: 1.2%, Ti: 2.0%, Al: 2.2%, Co: 1.9%, Zr: 0.01%, B: 0.02%, and the balance is Fe. The nickel-iron-based high-temperature alloy sample with the above composition is heated to 250°C above the γ′ dissolution temperature, and then kept warm for 2 hours. After the insulation is completed, it is quickly cooled to room temperature by water quenching; wherein the heating rate is 10°C / min. Then the nickel-iron-based high-temperature alloy sample is heated again to 170°C above the γ′ dissolution temperature, and then kept warm for 1.5 hours. After the insulation is completed, the sample is taken out and air-cooled for 2.5 minutes, and then quickly cooled to room temperature by water quenching; wherein the heating rate is 10°C / min.
[0062] Fig.13 The metallographic morphology of the alloy of Example 4 after heat treatment shows that the alloy matrix is austenite with a grain size of 132 μm. The alloy was analyzed by copper sulfate solution, and the grain boundary SEM morphology is as follows: Fig.14 As shown, it can be seen that the grain boundary has less MC and M 23 C6 carbide phase, carbide volume fraction is 5.5%. The alloy was analyzed by nitroglycerin solution, and the SEM morphology of the intragranular strengthening phase is as follows: Fig.15 As shown, the size of the precipitated phase in the crystal is 17nm, and the volume fraction is 14.2%. The alloy tube is flattened according to the "GB / T 246 Metal Material Tube Flattening Test Method". The results are as follows Fig.16 As shown, there are no cracks or fissures on the inner and outer surfaces of the sample.
[0063] Comparative Example 1
[0064] In this comparative example, the alloy composition is prepared according to the mass percentage. The specific contents of each component of the nickel-iron-based high-temperature alloy material sample of this comparative example are as follows: C: 0.05%, Si: 0.6%, Mn: 0.1%, Cr: 20%, P: 0.01%, Ni: 40%, Mo: 0.3%, W: 0.2%, Nb: 1.0%, Ti: 1.9%, Al: 1.8%, Co: 1.0%, Zr: 0.01%, B: 0.01%, and the balance is Fe. The nickel-iron-based high-temperature alloy sample with the above composition is heated to 240°C above the γ′ dissolution temperature, and then kept warm for 1 hour. After the insulation is completed, it is quickly cooled to room temperature by water quenching; wherein the heating heating rate is 10°C / min. Then the nickel-iron-based high-temperature alloy sample is heated again to 200°C above the γ′ dissolution temperature, and then kept warm for 2 hours. After the insulation is completed, the sample is taken out and air-cooled for 3 minutes, and then quickly cooled to room temperature by water quenching; wherein the heating heating rate is 10°C / min.
[0065] The alloy matrix obtained in this comparative example is an austenite structure with a grain size of 124 μm. The alloy was subjected to a copper sulfate solution for structural display. SEM showed that the grain boundaries had less MC and M 23 C6 carbide phase. The alloy was analyzed by nitroglycerin solution and the size of the intragranular strengthening phase was 26nm and the volume fraction was 17.2%. Fig.17 The alloy tube was flattened according to "GB / T 246 Metal Material Tube Flattening Test Method" and the results are shown as follows. Fig.18 As shown, the sample surface is cracked.
[0066] Comparative Example 2
[0067] In this comparative example, the alloy composition is prepared according to the mass percentage. The specific contents of each component of the nickel-iron-based high-temperature alloy material sample of this comparative example are as follows: C: 0.08%, Si: ≤0.3%, Mn: 0.1%, Cr: 18%, P: 0.007%, Ni: 48%, Mo: 0.3%, W: 0.5%, Nb: 0.2%, Ti: 2.2%, Al: 2.1%, Co: 2.0%, Zr: 0.02%, B: 0.01%, and the balance is Fe. The nickel-iron-based high-temperature alloy sample with the above composition is heated to 180°C above the γ′ dissolution temperature, and then kept warm for 2.5 hours. After the end of the heat preservation, it is quickly cooled to room temperature by water quenching; wherein the heating rate is 5°C / min. Then the nickel-iron-based high-temperature alloy sample is heated again to 100°C above the γ′ dissolution temperature, and then kept warm for 2 hours. After the heat preservation is completed, the sample is taken out and air-cooled for 5 minutes, and then quickly cooled to room temperature by water quenching; wherein the heating rate is 5°C / min.
[0068] The alloy matrix obtained in this comparative example is an austenite structure with a grain size of 120 μm. The alloy was subjected to a copper sulfate solution for structural display. SEM showed that the grain boundaries had less MC and M 23 C6 carbide phase. The alloy was analyzed by nitroglycerin solution and the size of the intragranular strengthening phase was 24nm and the volume fraction was 16.3%. Fig.19 The alloy tube was flattened according to "GB / T 246 Metal Material Tube Flattening Test Method" and the results are shown as follows. Fig. 20 As shown, the sample surface is cracked.
[0069] The room temperature tensile properties and impact toughness results of the samples obtained after processing the above-mentioned Examples 1 to 4 and Comparative Examples 1 and 2 are shown in Table 1.
[0070] Table 1
[0071] Yield Strength tensile strength Elongation Room temperature impact toughness Example 1 561MPa 987MPa 34% <![CDATA[117J / cm 2 ]]> Example 2 597MPa 996MPa 32% <![CDATA[124J / cm 2 ]]> Example 3 545MPa 1020MPa 40% <![CDATA[140J / cm 2 ]]> Example 4 563MPa 1018MPa 38% <![CDATA[135J / cm 2 ]]> Comparative Example 1 541MPa 923MPa 20% <![CDATA[80J / cm 2 ]]> Comparative Example 2 533MPa 910MPa 22% <![CDATA[83J / cm 2 ]]>
[0072] It can be seen from Table 1 that the samples of the alloy pipes obtained in Examples 1 to 4 have good strength and toughness, while the samples of the alloy pipes in Comparative Examples 1 and 2 have poor plasticity and toughness.
Claims
1. A method for aging treatment of nickel-iron-based high-temperature alloy material, characterized in that: include: The first heat treatment: the nickel-iron-based high-temperature alloy is heated to 150-250°C above the γ′ melting temperature, and then kept warm for 0.5-3.0 hours, and then quickly cooled after the end of the heat preservation; wherein the heating rate is 5-20°C / min; Second heat treatment: heat the nickel-iron-based high-temperature alloy after the first heat treatment to 80-200°C above the γ′ melting temperature, then keep it warm for 0.5-3.0h, air cool it for 2-5min after the insulation, and then cool it quickly to complete the aging treatment; the heating rate is 5-20°C / min.
2. The aging treatment method of a nickel-iron-based high-temperature alloy material according to claim 1, characterized in that: The rapid cooling method in both the first heat treatment and the second heat treatment is water quenching.
3. The aging treatment method for a nickel-iron-based high-temperature alloy material according to claim 1, characterized in that: After the first heat treatment, the grain size of the nickel-iron-based high-temperature alloy is 100-160 μm, the volume fraction of grain boundary carbides is below 4% and is primary carbides, and the size of intracrystalline γ′ phase precipitation is no more than 3 nm.
4. The aging treatment method of a nickel-iron-based high-temperature alloy material according to claim 1, characterized in that: After the second heat treatment, the matrix of the nickel-iron-based high-temperature alloy is austenite, the grain size is 110-135μm, and the grain boundary carbides are MC and M 23 C6, the volume fraction of carbides is less than 10%, the volume fraction of the intracrystalline γ′ phase precipitation is less than 15%, and the size of the precipitation phase is 14-20nm.
5. The aging treatment method for a nickel-iron-based high-temperature alloy material according to claim 1, characterized in that: In the second heat treatment, the start time of air cooling is calculated from the time when the surface of the nickel-iron-based high-temperature alloy begins to cool down, and the end time of air cooling is the time point when the nickel-iron-based high-temperature alloy enters the rapid cooling medium.
6. The aging treatment method for a nickel-iron-based high-temperature alloy material according to claim 1, characterized in that: When the sum of the mass percentages of the elements Ti and Al in the nickel-iron-based high-temperature alloy is ≥4.0%, the air cooling time in the second heat treatment is not more than 4 minutes.
7. The aging treatment method for a nickel-iron-based high-temperature alloy material according to claim 1, characterized in that: After the second heat treatment, the nickel-iron-based high-temperature alloy is in an under-aged state.
8. A nickel-iron-based high-temperature alloy material, characterized in that: The nickel-iron-based high-temperature alloy material is obtained by the aging treatment method described in any one of claims 1 to 7.
9. The nickel-iron-based high-temperature alloy material according to claim 8, characterized in that: The components of the nickel-iron-based high-temperature alloy include, in percentage by mass: C: 0.04% to 0.09%, Si: ≤0.8%, Mn: ≤0.3%, Cr: 15% to 25%, P: ≤0.02%, Ni: 35% to 48%, Mo: 0.3% to 0.9%, W: ≤0.7%, Nb: ≤1.5%, Ti: 1.0% to 3.0%, Al: 1.3% to 3.0%, Co: ≤3.0%, Zr: ≤0.05%, B: ≤0.02%, and the balance is Fe.
10. A nickel-iron-based high-temperature alloy material according to claim 8 or 9, characterized in that: The room temperature yield strength of the nickel-iron-based high temperature alloy is not less than 300 MPa, the elongation is not less than 30%, and the room temperature impact toughness is not less than 80 J / cm 2 .